Increased Expression of Serine Palmitoyltransferase (SPT) in Balloon-injured Rat Carotid Artery - Uhlinger, David J.; Carton, Jill M.; Argentieri, Dennis C.; Damiano, Bruce P.; D’Andrea, Michael R. (Thrombosis and Haemostasis, 2001)
The response to vascular injury is a complex wound healing response involving cell proliferation, migration, remodeling and inflammation. In the present studies we employed a rat balloon angioplasty model of vascular injury to investigate the potential role of sphingolipid signaling in the response to vascular injury. The enzyme serine palmitoyltransferase (SPT) catalyzes the first committed step in de novo sphingolipid biosynthesis. We observed marked upregulation of expression of both SPT subunits in actively proliferating cells in injured vessels. This enhanced SPT expression occurs in de-differentiated fibroblasts and proliferating vascular smooth muscle cells. The upregulation is particularly apparent in the proliferating luminal edge of the neointima and the adventitial de-differentiated fibroblasts and may serve as a hallmark of this process. The possible functional consequences of this enzyme upregulation and its role in the response to vascular injury are suggested but remain to be determined.
Keywords: Serine palmitoyltransferase -1 and -2; rat balloon angioplasty; restenosis; immunohistochemistry; reactive fibroblasts